KAJIAN ADSORPSI LOGAM CU DENGAN ADSORBEN SILIKA GEL - Wisnu Adi Prasojo; Srie Muljani (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
Adsorption is a separation process on a particular substance based on the affinity of a compound to a solid. The adsorption process requires an adsorbent as an absorbent material and an adsorbate as an absorbed component. The adsorbent that is often used to absorb Cu2+ ions is silica gel. Silica gel is a rigid gel that is amorphous. In silica gel there are two main bonding groups, namely siloxane and silanol groups which cause silica gel to easily absorb polar molecules, especially water. The purpose of this research is to get the best mass of silica and the effect of the initial concentration of Cu ions on the final concentration of Cu metal. In this study, two operating conditions were varied, namely the mass of silica gel adsorbent 0.4 grams; 0.6 grams; 0.8 grams; 1 gram; 1.2 grams and the initial concentration of Cu metal 3 ppm; 4 ppm; 5 ppm; 6 ppm; 7 ppm. The results of this study showed that the silica content of bagasse ash was 70.97% with a surface area of 283.802 m2/g. The best result of this study reduced the content of copper metal (Cu) by 88% in the condition of silica gel mass of 1.2 grams. The adsorption isotherm shows that the data is more in line with the Freundlich equation. The resulting equation is y = 0.4268x + 0.4969 with an R2 value of 0.9837.